A Thomas More Source Book - More, Thomas, Saint, 1478-1535; Smith, Stephen W., 1950-; Wegemer, Gerard, 1950- (Book collections on Project MUSE., 2004)
"This source book brings together classic text by and about Thomas More - poet, scholar, statesman, family man, educational reformer, philosopher, historian, and saint. In addition to serving as an introduction to More's life and writings for the general reader, this collection is a helpful companion to the study of More's literary and philosophical masterwork, Utopia, and to the study of sixteenth-century history, literature, philosophy, or politics."--Jacket